2007
DOI: 10.1152/japplphysiol.00293.2007
|View full text |Cite
|
Sign up to set email alerts
|

Progressive decrease of heart period variability entropy-based complexity during graded head-up tilt

Abstract: Complexity (or its opposite, regularity) of heart period variability has been related to age and disease but never linked to a progressive shift of the sympathovagal balance. We compare several well established estimates of complexity of heart period variability based on entropy rates [i.e., approximate entropy (ApEn), sample entropy (SampEn), and correct conditional entropy (CCE)] during an experimental protocol known to produce a gradual shift of the sympathovagal balance toward sympathetic activation and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
182
1
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(215 citation statements)
references
References 22 publications
27
182
1
5
Order By: Relevance
“…It is well-known that the complexity of HP, as estimated by the RMSCE of HP, is under vagal control at short time scale [12,13,15,42,43] and under sympathetic control at long time scale [12,13,15]. This study confirms these observations.…”
Section: Rmsce and Rmsse Reflect Day-night Variationssupporting
confidence: 87%
See 1 more Smart Citation
“…It is well-known that the complexity of HP, as estimated by the RMSCE of HP, is under vagal control at short time scale [12,13,15,42,43] and under sympathetic control at long time scale [12,13,15]. This study confirms these observations.…”
Section: Rmsce and Rmsse Reflect Day-night Variationssupporting
confidence: 87%
“…This finding suggested that having a reduced complexity of the cardiac control both at the level of sinus node and ventricles during DAY (i.e., when the arrhythmic risk is greatest in LQT1) is a protective factor [13]. Since AMCs are characterized by a more reactive sympathetic control [45] and a less reactive vagal regulation [45][46][47], this reduced complexity of the sympathetic control might be the result of the synchronization of neural inputs operating at slightly different temporal scales performed by the higher sympathetic driver [43,48]. However, this study added a new, relevant, piece of information.…”
Section: Rmsce and Rmsse Distinguish Lqt1 Individuals With Different mentioning
confidence: 99%
“…Approximate entropy did not change during graded head-up tilt in 17 healthy subjects, a finding which was explained to be due to the bias of considering self-matches. Instead, corrected approximate entropy, sample entropy and corrected conditional entropy showed a progressive decrease as a function of the tilt table inclination (Porta et al 2007a). This may indicate that a shift of the sympathovagal balance towards sympathetic activation and vagal withdrawal decreases the complexity of heart rate dynamics.…”
Section: (B ) Physiological Background Of Entropy Measures Of Rr Intementioning
confidence: 97%
“…The improved accuracy of SampEn statistics makes them useful in the study of experimental clinical cardiovascular and other biological time series (Richman and Moorman 2000). It has been established that complexity of beat-to-beat variability was controlled by the ANS (Porta et al 2007a): heartbeat complexity could be reduced by vagal blockade (Penttila et al 2003) when vagal activation increased complexity (Porta et al 2007b). Sympathetic excitation by pharmacological (Penttila et al 2003) or physiological method (Porta et al 2007a) reduced complexity and sympathetic blockade with propranolol increased irregularity of the HR (Lepoluoto et al 2005).…”
Section: Non-linear Domainmentioning
confidence: 99%
“…It has been established that complexity of beat-to-beat variability was controlled by the ANS (Porta et al 2007a): heartbeat complexity could be reduced by vagal blockade (Penttila et al 2003) when vagal activation increased complexity (Porta et al 2007b). Sympathetic excitation by pharmacological (Penttila et al 2003) or physiological method (Porta et al 2007a) reduced complexity and sympathetic blockade with propranolol increased irregularity of the HR (Lepoluoto et al 2005). FrD and SampEn of HR time series correlate highly with each other and also with the high-frequency power and hence appear to reflect vagal modulation of HR variability (Yeragani et al 1993).…”
Section: Non-linear Domainmentioning
confidence: 99%